2019
DOI: 10.3390/app9183893
|View full text |Cite
|
Sign up to set email alerts
|

Shoe Cushioning Effects on Foot Loading and Comfort Perception during Typical Basketball Maneuvers

Abstract: Purpose: This study aimed to explore the relationship between foot loading and comfort perception in two basketball shoes during basketball-specific maneuvers. Methods: Twelve male collegiate basketball players were required to complete three basketball maneuvers (i.e., side-step cutting, 90 • L-direction running, and lay-up jumping) in two basketball shoe conditions (shoe L and shoe N, with different midsole cushioning types). Two Kistler force plates and a Medilogic insole plantar pressure system were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous study reported the cushioned shoes showed overall lower plantar pressure than less cushioned shoes during landings [42]. Moreover, a significant difference was noted on the plantar pressure of two cushioned shoes during different basketball maneuvers due to the differences in the impact absorption ability of the midsole [43].…”
Section: Impact Forcesmentioning
confidence: 90%
“…Previous study reported the cushioned shoes showed overall lower plantar pressure than less cushioned shoes during landings [42]. Moreover, a significant difference was noted on the plantar pressure of two cushioned shoes during different basketball maneuvers due to the differences in the impact absorption ability of the midsole [43].…”
Section: Impact Forcesmentioning
confidence: 90%
“…Basketball shoes often include increased ankle support through ankle collar height and stiffness, however their effect on performance remains trivial (Brizuela et al, 1997;Liu et al, 2017). Also noteworthy, while these findings may seem to challenge the ergogenic benefit of Basketball shoes, jumping is only one component of the sport-specific movements required during play and other factors should be considered Mohr et al, 2016;Vienneau et al, 2015;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…15 and explosiveness through their lightweight constructs and materials (Vienneau et al, 2015). Complementing the ergogenic benefits, basketball shoes may also be considered personal protection equipment (PPE) during play, as a large emphasis in their design has concomitantly focused on mitigating injury risk (Brizuela et al, 1997;Fu et al, 2014;Liu et al, 2017;Zhang et al, 2019). Basketball shoes are equipped with added cushion to attenuate forces between the foot and hardwood surface, which may be particularly valuable during jumps and landings as ground reaction forces during jump take-off may exceed upwards of three-fold bodyweight and may exceed seven-fold body weight during landing (McClay et al, 1994).…”
Section: Does Footwear Influence Countermovement Jump Parameters Used To Assess Performance In Collegiatementioning
confidence: 99%
“…Footwear comfort perception encompasses the overall footwear experience, which is highly influenced by individual preference (Mundermann, Nigg, Humble, & Stefanyshyn, 2003). Several objective and subjective footwear characteristics such as fit (Hurst, Branthwaite, Greenhalgh, & Chockalingam, 2017; Witana, Goonetilleke, Au, Xiong, & Lu, 2009), cushioning (Dinato et al, 2015; Zhang et al, 2019), weight and even appearance (Williams & Nester, 2006) alongside perception of ride (Agresta et al, 2020), pain (Stevens, Mauger, Hassmèn, & Taylor, 2018), fatigue and running speed (Hintzy, Cavagna, & Horvais, 2015) can influence individual overall comfort perception. Partially tailoring footwear with custom foot orthoses could potentially improve comfort perception (Mills, Blanch, & Vicenzino, 2011).…”
Section: Introductionmentioning
confidence: 99%